Preconditioning of mesenchymal stromal cells toward nucleus pulposus‐like cells by microcryogels‐based 3D cell culture and syringe‐based pressure loading system. Issue 3 (19th November 2015) - Zeng, Yang; Feng, Siyu; Liu, Wei; Fu, Qinyouen; Li, Yaqian; Li, Xiaokang; Chen, Chun; Huang, Chenyu; Ge, Zigang; Du, Yanan
Abstract: To precondition mesenchymal stromal/stem cells (MSCs) with mechanical stimulation may enhance cell survival and functions following implantation in load bearing environment such as nucleus pulposus (NP) in intervertebral disc (IVD). In this study, preconditioning of MSCs toward NP‐like cells was achieved in previously developed poly (ethylene glycol) diacrylate (PEGDA) microcryogels (PMs) within a syringe‐based three‐dimensional (3D) culture system which provided a facile and cost‐effective pressure loading approach. PMs loaded with alginate and MSCs could be incubated in a sealable syringe which could be air‐compressed to apply pressure loading through a programmable syringe pump. Expression levels of chondrogenic marker genes SOX9, COL II, and ACAN were significantly upregulated in MSCs when pressure loading of 0.2 MPa or 0.8 MPa was implemented. Expression levels of COL I and COL X were downregulated when pressure loading was applied. In a nude mouse model, MSCs loaded in PMs mechanically stimulated for three days were subcutaneously injected using the same culture syringe. Three weeks postinjection, more proteoglycans (PGs) were deposited and more SOX9 and COL II but less COL I and COL X were stained in 0.2 MPa group. Furthermore, injectable MSCs‐loaded PMs were utilized in an ex vivo rabbit IVD organ culture model that demonstrated the leak‐proof function and enhanced cell retention of PMs assisted cell delivery to a load bearing environment for potential NP regeneration. This microcryogels‐based 3D cell culture and syringe‐based pressure loading system represents a novel method for 3D cell culture with mechanical stimulation for better function. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 507–520, 2017.